Factors related to Icelandic student teachers' prospective commitment to the teaching profession. Issue 2 (2021) - Elstad, Eyvind; Björnsdóttir, Amalía; Christophersen, Knut-Andreas; Jóhannsdóttir, Þuríður Jóna; Turmo, Are
No abstract available